Multi-Criteria Decision-Making with Novel Pythagorean Fuzzy Aggregation Operators. (18th April 2023) - Al-Shamiri, Mohammed M.; Ismail, Rashad; Mazher Qurashi, Saqib; Dilawar, Fareeha; Ahmed Shami, Faria
Abstract : Unpredictability and fuzziness coexist in decision-making analysis due to the complexity of the decision-making environment. "Pythagorean fuzzy numbers" (PFNs) outperform "intuitionistic fuzzy numbers" (IFNs) when dealing with unclear data. The "Pythagorean fuzzy set" (PFS) is a useful tool because it removes the restriction that the sum of membership degrees be less than or equal to one by substituting the square sum for the sum of membership degrees. This study proposes two aggregating operators (AOs). The recommended operators outperform the already specified PFN operators. The proposed operator is utilised in the multicriteria decision-making process to identify the best candidate for instruction (MCDM).